Renarrating and Framing of Religious History in the Translation of Ali Abdel Razek’s ‘Islam and the Foundations of Political Power’ - Babban, Nasouh Abdul Fattah (جامعة النجاح الوطنية, 2020)
This study draws on Mona Baker’s notion of ‘renarration’ as a new metaphor for translation in order to examine a book by the Egyptian Muslim orthodox author (Al Azhar scholar) Ali Abdel Razek, in the context of the Muslim dominant narrative and the power of the Muslim scholars over translation, which turned the discipline into an ideological entrapment. The book by Abdel Razek, ‘Islam and the Foundations of Political Power’ (1925), which was translated into English by Maryam Loutfi and edited by Abdou Filali-Ansary in 2012, narrates the Muslim religious history in a marked contrast to the Muslim prevailing narrative which Muslims believe to come straight from authoritative sources and is characterized by the use of skillfully written and breathtaking anti-ideology statements (Islam is a religion, not a state). In all Muslim controlling narratives, ideology is linked to translation: It stands for the cultural conflict between Islam and the West. The Muslim superior narrative is a particularly sensitive issue to which translators should adhere and reject other narratives which can possibly give a bad image about Islam. This study investigates the possible reasons for the extremely negative feedback received about Abdel Razek’s book for about a century. Baker’s narrative theory: typology, features and strategies of framing and assessment are applied to the translation of the book to establish a claim that Baker’s ideology-driven analytical tools are of very little use in the first place as researchers from diverse backgrounds will draw similar, if not typical, conclusions with or without the employment of Baker’s parameters. The strength of Baker’s theoretical categories is less likely to have any real effect on the researcher. It seems that Baker’s version of the theory is unproductive as far as religion, history and politics in Islam are concerned. It usually takes the researcher a deep understanding of the Muslim dominant narratives to analyze Muslim religious, political and historical translations: just interpret the translations in a marked contrast to the dominant narratives. In this sense, it also takes the well-informed translator little effort to dig the Muslim heritage and come up with Muslim narratives that deviate from and contradict the dominant ones; those will surely meet the target audience’s taste, needs and desires. The mere translation of a contradicting narrative is an act of framing in itself. To a great extent, the translator of the book in question was faithful to the source text even at the cost of the final product’s readability and naturalness, simply because the book conveys a different message than the Muslim prevailing narrative and the translator did not have to elicit a different response than the source text and its paraphernalia. As far as ideology is concerned, an analysis of the application of Baker’s narrative theory to an area of inquiry conducted by a Muslim researcher would inevitably conclude that translation was not up to par regardless of its several advantages; whereas the analysis of the same translation conducted by ‘the other’ would highlight the translation’s uniqueness and greatness regardless of its obvious flaws and deficiencies.
إعادة رواية التاريخ الديني وتأطيره في ترجمة كتاب الاسلام وأصول الحكم لعلي عبدالرازق